BITCOIN CRYPTOCURRENCY PRACTICES SHARIA MAQASHID PERSPECTIVE - Yuniartik Yuniartik (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
Cryptocurrency is a digital currency created using cryptographic technology to secure transactions and control the creation of new units. Cryptocurrencies are not managed by any financial institution or government, so transactions made using cryptocurrencies are usually more anonymous than transactions made using fiat currency. Cryptocurrencies can be stored and exchanged through special applications or "wallets" available online. Some examples of popular cryptocurrencies are Bitcoin, Ethereum, and Litecoin. Bitcoins are digital currency created in 2009 by someone or the using group name the pseudonym of Satoshi Nakamoto. Bitcoins operate with use blockchain technology, that is a network as decentralized as possible every transaction recorded and verified digitally. Blockchain makes bitcoin and other digital currencies possible for exchanged without need involve a bank or institution finance other. This study aims to determine the Muqashid Syariah Perspective Bitcoin Cryptocurrency Transaction Practices. This study uses a normative method, namely research to find concrete laws from the practice of using the Bitcoin currency as a means of payment transactions, which are appropriate or not in practice based on the provisions of Islamic law. This research is a type of library research ( library research ) using library materials as the main data source. The results of this study indicate that there are maslahah and mafsada in bitcoin cryptocurrency from a sharia muqashid perspective. Mafsadat of bitcoin include: first, cryptocurrency is a decentralized currency system that only depends on the system and users, and has no consumer protection. Second, mining fees are too high and keep increasing as time goes on. Third, unmanageable price fluctuations. While the maslahah of bitcoin include: first, Bitcoin will never experience inflation. Second, the bitcoin cryptocurrency makes transactions faster compared to other currency systems. Thirdly, cryptocurrency is an open and distributed ledger that permanently records all transactions and can solve the problem of double spending. Fourth, transaction fees are very cheap or even free.